Pengaruh Sanksi Pajak Dan Kualitas Pelayanan Terhadap Kepatuhan Wajib Pajak Dalam Membayar Pajak Bumi Dan Bangunan (PBB) (Studi Kasus Pada Badan Pendapatan Daerah UPT PPD Wilayah Bandung Tengah) - Ramadhani Zafran; Tria Apriliana (Journal of Economic, Bussines and Accounting (COSTING), 2023)
This study aims to determined and analyzed the effect of tax sanctions on taxpayer compliance, to determine and analyze the effect of service on taxpayer compliance and to determine and analyze the effect of tax sanctions and service quality on taxpayer compliance. In this study the method used is an explanatory survey. The data collection technique used in this study used a questionnaire technique with a sample of 100 people. Data processing techniques using editing, coding and tabulation. Data analysis techniques used descriptive statistical tests, validity tests, reliability tests, classic assumption tests, normality tests, multicollinearity tests, heteroscedasticity tests, multiple linear regression analysis, T tests, F tests, and analysis of the coefficient of determination. Based on the research results, tax sanctions affect taxpayer compliance registered with the Regional Revenue Agency UPTD PPD in the Central Bandung region with a t-count of 2,959 > t-table (1,984) and has a significance value of 0.004, less than 0.050. This means that the better the tax sanctions applied, the better the taxpayer compliance will be. Based on the research results, service quality affects taxpayer compliance registered with the UPTD PPD Regional Revenue Agency for the Central Bandung Region. This means that the better the quality of services provided, the better the Taxpayer Compliance based on the comparison between tcount and ttable which shows tcount of 5,172, while ttable is (1,984). From these results it could be seen that tcount > ttable, namely 5,172 > 1,984. Based on the results of research on Tax Sanctions and Service Quality, they simultaneously influence taxpayer compliance registered at the Regional Revenue Agency UPTD PPD in the Central Bandung Region with F count greater than F table value, namely 86,296 > 3,089, with a significance value of 0.000 <0.050. Keywords: Tax Sanctions, Service Quality, Taxpayer Compliance